Faktor-Faktor yang Mempengaruhi Kecemasan pada Pasien yang Akan Menjalani Kateterisasi Jantung di Rumah Sakit Murni Teguh Medan - Renti Sinurat; Afnijar Wahyu (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Background: Cardiac catheterization is the most widely used diagnostic and hemodynamic intervention procedure in the world for the treatment of coronary heart disease (CHD). Cardiac catheterization can cause anxiety in patients who will undergo it. Objective: To analyze the factors that influence the anxiety of patients who will undergo cardiac catheterization. Method: This study is a descriptive analytical study with a cross-sectional approach conducted at Murni Teguh Memorial Hospital Medan. The study population was 40 people, and all of them were used as samples (total sampling). The research instrument was a questionnaire. Data analysis was carried out univariately and bivariately using the Chi-Square test with a significance level of 95% (= 0.05). Results: This study shows that there is a significant influence between knowledge, family support, past experience, and education level on the anxiety of patients who will undergo cardiac catheterization at Murni Teguh Hospital Medan. This is proven by the chi square test with p values for each knowledge (p = 0.000); family support (p = 0.002); past experience (p = 0.003); and education (p=0.003) which are all less than 0.005. Conclusion: Cardiac catheterization patient anxiety is influenced by knowledge, family support, past experience, and education level. Suggestion: It is recommended that further researchers increase the number of samples and independent variables, considering that many factors influence patient anxiety before cardiac catheterization/angiography